ANALISIS BAURAN PEMASARAN DAN PELAYANAN YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN DI STARBUCKS BEACHWALK MALL, BADUNG - Kirana A, Nadya; Wiranatha, Agung Suryawan; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 1 (2018): MaretDO - 10.24843/JRMA.2018.v06.i01.p03, 2018)
The objectives of research were to determine the factors of marketing mix and service that influenc consumer purchase/buying decisions at Starbucks Beachwalk Mall in Badung and determine the dominant variables that represent every factors influencing purchasing decisions at Starbucks Beachwalk Mall in Badung. Data collection was conducted by distributing 72 questionnaires to the respondents. The data obtained was analyzed using factor analysis method. The results show that there were 8 factor by, namely factor 1 is formed by 4 variables: the accuracy of promotional targets, access, promotion quality, timely service with eigenvalue of 3.179. Factor 2 consists of 4 variables: attractive product appearance, attractive packaging, discount, accurate service with eigenvalue value of 2,296. Factor 3 is formed by 3 variables: proper time of promotion, affordability, spacious parking lot, safe and comfortable with an eigenvalue value of 1.760. Factor 4 is formed by 2 variables: price equilibrium with product quality, business location can be seen clearly from normal distance with eigenvalue value of 1.449. Factor 5 is formed by 2 variables: the existence of other support services, ease of service with eigenvalue value of 1.416. Factor 6 is formed by 2 variables: good taste of coffee, specialty coffee products with eigenvalue value of 1.173. Factor 7 is formed by 2 variables: promotion quantity, polite and friendly service with eigenvalue value of 1.078. Factor 8 is formed by 2 variables: convenience of getting service, promotion of sales through promotion media with value eigenvalue equal to 1,000 Keywords: Factor analysis, marketing mix, purchase decisions, starbucks coffee